Socio-Economic Life of Migrant Workers' Wives - Khoirul Miftah; Su’adah Su’adah; Luluk Dwi Kumalasari (Jurnal Perempuan dan Anak, 2022)
Karangtawar Village, Laren District, is located in Lamongan district, where many people, especially the head of the family, become migrant workers, so that wives whose husbands leave them as migrant workers take on two roles to take care of family life at home, whether it's educating their children directly or looking for busyness in public spaces. because to fill social activities or help additional family economy. Like what Alfred Schutz said that human actions become a social relationship when humans give a certain meaning or meaning to their actions, and other humans also understand their actions as meaningful. It will not be separated from the behavior or interactions carried out by the wives of migrant workers. Migrant workers' wives will give a certain meaning or meaning to their actions and other people will understand what migrant workers' wives do. This research was conducted to answer a phenomenon that occurred in the Karangtawar Village community related to the socio-economic life of the wives of migrant workers. In the social life of the wives of migrant workers, apart from their domestic activities, they also carry out public activities such as teaching, establishing good relations with other communities and carrying out other social activities.